PENGARUH LATIHAN CIRCUIT TRAINING TERHADAP DAYA TAHAN TUBUH - Aldi Septia (Journal of Physical Education and Sport Science, 2022)
The Effect of Circuit Training on Body Endurance of Football Extracurricular Players at SMA Negeri 1 Cibingbin, Kuningan Regency". The purpose of this study was to determine: The Effect of Circuit Training on the Endurance Ability of Soccer Players at SMA Negeri 1 Cibingbin, Kuningan Regency. This study uses experimental research methods. The population and sample in this study were football extracurricular players totaling 17 players. With the sampling technique using saturated samples, in order to obtain a sample of 17 players. The research instrument used in this study was the Body Endurance test. The data analysis technique in this study used normality test, homogeneity test and hypothesis testing.The results of the analysis and processing of pre-test data obtained the lowest time of 14.04, the highest time of 15.39. While the post-test data obtained the lowest time is 13.13, the highest time is 15.29. This shows an increase in the endurance ability of football players. Based on the test, it shows that the two tests have a normal distribution. Therefore, to test the hypothesis using the paired sample t-test, the pre-test and post-test values ​​showed a sig. (2-tailed) value of 0.000 <0.05, so there was a significant difference. So H0 is rejected and Ha is accepted. This means that the Effect of Circuit Training on the Body Endurance of Football Extracurricular Players at SMA Negeri 1 Cibingbin, Kuningan Regency